A new hyladelphine marsupial (Didelphimorphia, Didelphidae) from cave deposits of northern Brazil - Oliveira, Édison Vicente (2011)
Based on very small upper and lower molars recovered from the Quaternary limestone caves in the State of Tocantins, northern Brazil, we describe a new genus and species of a didelphimorphian marsupial. A phylogenetic analysis based on morphological + karyotypic data set recovered the new genus and species as the sister taxon to the living didelphid, Hyladelphys kalinowskii Voss, Lunde & Simons. The new taxon differs from the latter in having a slightly larger size, more inflated and blunt cusps, greater reduction in number and size of the stylar cusps, in the absence of an anterior cingulum, a deeper ectoflexus in M2, paracone and metacone subequal in M2, and narrower and eccentric protocones. The new marsupial probably weighed no more than 40 g and its molar morphology is suggestive of mixed, insectivorous-frugivorous feeding habits. Although we regard the fauna of Gruta dos Mouras cave as Pleistocene, we do not negate the possibility that a temporal mixing (“time-averaging”) of Pleistocene and Holocene specimens existed and that the newly described taxon is a living marsupial in the study area.